Reviving Antibiotics: Efflux Pump Inhibitors That Interact with AcrA, a Membrane Fusion Protein of the AcrAB-TolC Multidrug Efflux Pump - Abdali, Narges (ACS Infect Dis, 2016)
Antibiotic resistance is a major threat to human welfare. Inhibitors of multidrug efflux pumps (EPIs) are promising alternative therapeutics that could revive activities of antibiotics and reduce bacterial virulence. Identification of new druggable sites for inhibition is critical for the development of effective EPIs, especially in light of constantly emerging resistance. Here, we describe EPIs that interact with periplasmic membrane fusion proteins, critical components of efflux pumps that are responsible for the activation of the transporter and the recruitment of the outer-membrane channel. The discovered EPIs bind to AcrA, a component of the prototypical AcrAB-TolC pump, change its structure in vivo, inhibit efflux of fluorescent probes, and potentiate the activities of antibiotics in Escherichia coli and other Gram-negative bacteria. Our findings expand the chemical and mechanistic diversity of EPIs, suggest the mechanism for regulation of the efflux pump assembly and activity, and provide a promising path for reviving the activities of antibiotics in resistant bacteria.